2021
DOI: 10.1038/s41598-021-00689-6
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic corrosion inhibition from aspect of bonding orbital theory in Cu/Ru barrier CMP

Abstract: In this report, the galvanic corrosion inhibition between Cu and Ru metal films is studied, based on bonding orbital theory, using pyridinecarboxylic acid groups which show different affinities depending on the electron configuration of each metal resulting from a π-backbonding. The sp2 carbon atoms adjacent to nitrogen in the pyridine ring provide π-acceptor which forms a complex with filled d-orbital of native oxides on Cu and Ru metal film. The difference in the d-orbital electron density of each metal oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The higher R 2 value of the Langmuir model compared to that of the Freundlich model indicates that the picolinic acid was homogeneously adsorbed on tungsten oxide [18,19], meaning that the picolinic acid forms a monolayer on the surface of tungsten oxide [18]. Both Lee et al and Ramis et al experimentally demonstrated that the strong Lewis acid sites and Brønsted acid sites on the surface of metal oxide films could be active sites for the adsorption of pyridine functional groups [11,20,21]. From this point of view, the coordinated covalent bonding between the pyridine group of picolinic acid and the acidic sites of tungsten oxide resulted in monolayer adsorption on the surface of tungsten oxide [12,13,20,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher R 2 value of the Langmuir model compared to that of the Freundlich model indicates that the picolinic acid was homogeneously adsorbed on tungsten oxide [18,19], meaning that the picolinic acid forms a monolayer on the surface of tungsten oxide [18]. Both Lee et al and Ramis et al experimentally demonstrated that the strong Lewis acid sites and Brønsted acid sites on the surface of metal oxide films could be active sites for the adsorption of pyridine functional groups [11,20,21]. From this point of view, the coordinated covalent bonding between the pyridine group of picolinic acid and the acidic sites of tungsten oxide resulted in monolayer adsorption on the surface of tungsten oxide [12,13,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the selective adsorption mechanism of pyridine functional groups from the aspect of bonding orbital theory was suggested in copper barrier CMP [11]. Herein, we extended it to the tungsten application using α-picolinic acid as an inhibitor to prevent tungsten dissolution, and its impact on tungsten topography was discussed.…”
Section: Introductionmentioning
confidence: 96%
“…21,22 The ring structure's planar (flat) configuration further increases the adsorption on the metal surface and better protects it from corrosion. 23 The global hardness measures molecular stability and reactivity. 17 Hard molecules typically have large band gap energy since the inhibitors' reactive sites could only adsorb strongly on the metal surface when the chemical hardness value is at the lowest.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the highest electron affinity of TADH (1.79 eV) meant a highly specific binding with the metal surfaces. This is due to the strong interaction between the π-electron of the ring structure, which contributes to more robust protection layers on the metal surface. , The ring structure’s planar (flat) configuration further increases the adsorption on the metal surface and better protects it from corrosion …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the electrochemical impedance spectroscopy (EIS) technique is widely used to investigate the electrochemical behaviour of a slurry in the CMP of Al, 28 Cu, 29,30 Ru 31,32 etc. In this study EIS is used to characterize the interaction between the phase change materials and the slurry.…”
Section: Introductionmentioning
confidence: 99%